Elimination of Plant Pathogenic Bacteria by Solar Ultraviolet Radiation in Hydroponic Systems - Rouhollah Farhadi; Rahman Farrokhi Teimourlou; Youbert Ghosta (Journal of Agricultural Sciences)
Removing plant pathogens with the sun as a free, available, clean, and sustainable source of energy is interesting. However, there is no data for disinfecting major plant pathogenic bacteria such as Pseudomonas syringae and Clavibacter michiganensis subsp. michiganensis by solar ultraviolet radiation. To obtain the required time for killing these bacteria at different temperatures, a bacterial suspension of active growing cells (approximately 107 CFU mL-1) was prepared and subjected to heat inside a water bath. The minimum required time for killing both of the bacteria was achieved 420, 45, and 15 min at 50, 55, and 60 °C, respectively. To examine the effect of solar ultraviolet radiation, the bacteria suspensions inside a quartz tube were exposed to the sun on a horizontal surface at the constant temperature of 50 °C within the water bath (water depth: 0.1 m). Both of the bacteria were killed after one hour by receiving 95.481 kJ m-2 ultraviolet and 2.79315 MJ m-2 solar radiation doses. The synergy of heat and solar UV could considerably reduce the killing time of the bacteria (7 to 1 hours) at 50 °C. The recommended solar UV dose is 95.481 kJ m-2 for this condition.